Discovery of cold tolerance genes and favorable alleles in Kam sweet rice across various growth stages - Kunchi Yu; Chunhui Liu; Joohyun Lee; Xiaoding Ma; Bing Han; Zhengwu Zhao; Soon-Wook Kwon; Longzhi Han; Di Cui (Theoretical and Applied Genetics, 2026)

Protocol for the purification and culture of primary retinal ganglion cells and development of common pathological models - Xiaoding Shui; Yan Wang; Yu Luo; Xiaoyu Liang; Tao Chen; Yanting Xia; Qiping Wei; Liang Liao (Journal of Molecular Histology, 2025)

Advances in Supercell Storm Research - Xiuming Wang; Huan Tang; Xiaoding Yu; Yuhao Zheng; Chenxi Wang; Haiyan Fei (Journal of Meteorological Research, 2025)

High-Precision Surfacing Position Prediction for Underwater Gliders via Coordinate Transformation - Yaojian Zhou; Mengjiao Kang; Jiancheng Yu; Jisong Bai; Tong Xue; Xiaoding Cheng (Journal of Marine Science and Engineering, 2025)
The accurate prediction of the surfacing position of underwater gliders (UGs) is critical for mission success and cost-effective retrieval. However, current state-of-the-art (SOTA) methods often rely on complex multi-model integrations or large volumes of ocean current data, thereby increasing operational costs and system complexity. In this study, we systematically introduce—for the first time—a coordinate-transformation-based prediction framework, originally applied in other navigation contexts, into the UG surfacing-position-prediction task. By projecting both the glider’s entry and surfacing positions into a Universal Transverse Mercator (UTM) planar coordinate system and treating the resulting displacement as the prediction target, we avoid dependence on heavily parameterized current models, simplify the training process, and maintain robust predictive accuracy. Our approach combines common machine learning predictors (e.g., AdaBoost, LGBM, gradient boosting, random forest, decision trees) instead of advanced deep learning architectures, thus reducing computational overhead. Experiments on two real-world sea trial datasets (containing 2159 and 1456 profiles, respectively) show that, compared with direct regression approaches, this method improves positioning accuracy by up to 50% within a 500-meter range, yet requires minimal multi-source data. Overall, this study integrates the concept of coordinate transformation into the task of predicting the surfacing position of underwater gliders, effectively streamlining the method without sacrificing accuracy. The result is a highly flexible and cost-effective approach, providing theoretical support for future optimizations of underwater glider navigation systems.

Influence of Irregular Coastlines on a Tornadic Mesovortex in the Pearl River Delta during the Monsoon Season. Part I: Pre-storm Environment and Storm Evolution - Lanqiang Bai; Dan Yao; Zhiyong Meng; Yu Zhang; Xianxiang Huang; Zhaoming Li; Xiaoding Yu (Advances in Atmospheric Sciences, 2024)

Synoptic-Scale Analysis on Development and Maintenance of the 19–21 July 2021 Extreme Heavy Rainfall in Henan, Central China - Dorina Chyi; Xiuming Wang; Xiaoding Yu; Junhui Zhang (Journal of Meteorological Research, 2023)

A novel ethylene-responsive factor IbERF4 from sweetpotato negatively regulates abiotic stress - Yang Yu; Ho Soo Kim; Peiyong Ma; Zhaodong Jia; Xiaoding Guo; Yizhi Xie; Sang-Soo Kwak; Peng Zhang; Xiaofeng Bian (Plant Biotechnology Reports, 2020)

Development of recycled polylactic acid/oyster shell/biomass waste composite for green packaging materials with pure natural glue and nano-fluid - Dingtian Xiao; Shan Qing; Pengfei Chen; Zhifeng Yu; Huaqiang Xiao; XiaoDing Wang (Environmental Science and Pollution Research, 2020)

Advances in Severe Convection Research and Operation in China - Xiaoding Yu; Yongguang Zheng (Journal of Meteorological Research, 2020)

Diachronic analysis of genetic diversity in rice landraces under on-farm conservation in Yunnan, China - Di Cui; Jinmei Li; Cuifeng Tang; Xinxiang A; Tengqiong Yu; Xiaoding Ma; Enlai Zhang; Guilan Cao; Furong Xu; Yongli Qiao; Luyuan Dai; Longzhi Han (Theoretical and Applied Genetics, 2016)

Climate analysis of tornadoes in China - Yeqing Yao; Xiaoding Yu; Yijun Zhang; Zijiang Zhou; Wusan Xie; Yanyu Lu; Jinlong Yu; Lingxiang Wei (Journal of Meteorological Research, 2015)

On eastern Asian dust storm - Zhao Bolin; Yu Xiaoding (Advances in Atmospheric Sciences, 1990)